Study on the Chinese Subfamily Anabropsinae (Orthoptera: Anostostomatidae) VI: One new species of Anabropsis (Pteranabropsis) from Yunnan Province - Lu, Xiangyi; Zhang, Qianwen; Bian, Xun (Zootaxa, 2022)
This paper is sixth study the Chinese Anabropsinae and reports one new species from Yunnan Province, China, viz. A. (Pteranabropsis) maguanensis sp. nov. (Chinese name: 马关黯螽). Meanwhile, the complete mitochondrical genome of the new species was determined and annotated. The 15, 962 bp circle genome consisted of 13 protein-coding, 22 transfer RNA, 2 ribosomal RNA genes, and an A+T-rich region. It has the typical invertebrate mitochondrial gene arrangement. All protein-coding genes (PCGs) were initiated by typical ATN codon. The nucleotide compositions were significant bias towards AT. All transfer RNA (tRNA) genes had a typical clover-leaf structure, except trnS1 in which the base pairs of the dihydrouridine (DHU) arm was lacking. Overall, six domains and 49 helices were predicted for rrnL, and three structural domains and 27 helices were predicted for rrnS.